Trace element concentrations in the apex predator swordfish (Xiphias gladius) from a Mediterranean fishery and risk assessment for consumers. Issue 1 (15th July 2017) - Gobert, S.; Pasqualini, V.; Dijoux, J.; Lejeune, P.; Durieux, E.D.H.; Marengo, M.
Abstract: Swordfish ( Xiphias gladius L., 1758) is an apex predator, highly migratory meso-pelagic fish widely distributed in the Atlantic Ocean and Mediterranean. As top predators, this fish may be the end reservoir of the bioaccumulation of trace elements in a food chain because they occupy higher trophic levels and are an important food source, causing them to be potentially hazardous to consume. This study aims to investigate the concentration of 18 trace elements of Swordfish, caught in the Mediterranean Sea and to discuss human exposure risks. The mean element levels in the fish muscles were clearly below the maximum allowable concentrations established by International food safety regulations. The data suggested that the risk is minor and acceptable for human health. The findings of this study amplify the scarce database on contaminants available, especially new data on "emerging elements", for this species from the Mediterranean Sea. Highlights: The element levels were below the maximum allowable concentrations. The data suggested that the risk is minor and acceptable for human health. The study amplifies the scarce database on contaminants from the Mediterranean Sea.